The Principal’s Management in Implementing a Love-Based Curriculum Through the Utilization of Artificial Intelligence at MTsN 1 Pasangkayu - Sadri (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to analyze the management of the madrasa principal in implementing the Love-Based Curriculum through the utilization of Artificial Intelligence (AI) at MTsN 1 Pasangkayu. The research employed a qualitative approach with a case study design. The participants consisted of the madrasa principal, vice principal for curriculum affairs, teachers, and educational staff. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that the madrasa principal implemented management strategies through program planning, strengthening digital literacy, teacher training, and continuous academic supervision. The implementation of the Love-Based Curriculum integrated values of compassion, empathy, tolerance, and spirituality into technology-based learning activities. The use of Artificial Intelligence assisted teachers in preparing learning materials, interactive media, and effective learning evaluations. This study concluded that adaptive and innovative madrasa management successfully supported the implementation of a technology-integrated Love-Based Curriculum to improve learning quality and teachers’ professional competence in the madrasa environment.